2013
DOI: 10.1074/jbc.m112.415224
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Controls p38 Activation to Promote Cell Survival under Genotoxic Stress

Abstract: Background:The role of autophagy in genotoxic stress remains poorly understood. Results: Autophagy deficiency sensitizes cells to UVB-induced apoptosis through p62-dependent p38 activation. Conclusion: Inhibition of autophagy promotes apoptosis following UVB damage by increasing p38 activation. Significance: These findings identify the vital role of autophagy in cell survival under genotoxic stress and suggest the function of autophagy in cancer pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
92
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 54 publications
3
92
1
Order By: Relevance
“…Our results are consistent with those of Qiang et al [22], who showed that autophagy-associated decreases in p38 phosphorylation enhances cell survival [22]. p38 activity was also found to be reduced in human SCCs, compared to normal human skin [22]. Moreover, inhibition of p38 signaling was associated with a defect in global genome nucleotide excision repair (GG-NER), a vitally important tumor protective pathway that recognizes and excises UVB-induced CPDs (cyclobutane pyrimidine dimers) and 6-4PPs (pyrimidine (6-4) pyrimidone photoproducts) that would otherwise be mutagenic [36].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with those of Qiang et al [22], who showed that autophagy-associated decreases in p38 phosphorylation enhances cell survival [22]. p38 activity was also found to be reduced in human SCCs, compared to normal human skin [22]. Moreover, inhibition of p38 signaling was associated with a defect in global genome nucleotide excision repair (GG-NER), a vitally important tumor protective pathway that recognizes and excises UVB-induced CPDs (cyclobutane pyrimidine dimers) and 6-4PPs (pyrimidine (6-4) pyrimidone photoproducts) that would otherwise be mutagenic [36].…”
Section: Discussionsupporting
confidence: 94%
“…74,75,91,93 Thus, we hypothesize that after low doses of DNA damage, autophagy activation by these transcription factors would result in clearance of membrane-permeabilized mitochondria, 94 generation of dNTPs and/or ATP for DNA repair activity, 47,48 degradation of pro-apoptotic proteins such as active caspase 8 95 and elimination of p62, thus preventing p38-hyperactivation. 96 Supporting the role of p53 in autophagy and cell survival, p53 mediates the transcription of parkin, 97 suggesting that p53 could regulate transcription of mitophagy genes in response to genomic damage, thus counterbalancing mitochondrial apoptotic signaling.…”
Section: Parpmentioning
confidence: 99%
“…123 Similarly, MSI-positive colon cancer cells with monoallelic deletions of UVRAG or UVRAG-KD HEK cells did not show reduced autophagy. Indeed, UVRAG participates in an autophagy-independent manner in preventing centrosome overduplication and chromosome missegregation during anaphase 124 as well as Increased apoptosis 96 in endocytic trafficking of EGFR, whose accumulation may enhance growth factor receptor signaling, thus supporting tumor growth. 125 Therefore, an autophagy-centric interpretation must always bear in mind these other functions described for the 'autophagy' genes.…”
Section: Parpmentioning
confidence: 99%
“…Although most studies indicate a cytoprotective role for autophagy, some evidence suggests that it contributes to cell death in response to oxidative stress. [13][14][15][16][17] Studies have also indicated that autophagy may be suppressed in response to oxidative stress, thereby sensitizing certain cells to apoptosis. 18,19 Unc-51-like kinase/autophagy 1 (ULK1/ATG1) is a mammalian serine-threonine kinase that regulates flux through the autophagy pathway by activating the VPS34 PI(3) kinase complex and facilitating ATG9-dependent membrane recycling.…”
mentioning
confidence: 99%